Local Photothermal Control of Phase Transitions for On‐Demand Room‐Temperature Rewritable Magnetic Patterning. Issue 22 (21st April 2020) - Mei, Antonio B.; Gray, Isaiah; Tang, Yongjian; Schubert, Jürgen; Werder, Don; Bartell, Jason; Ralph, Daniel C.; Fuchs, Gregory D.; Schlom, Darrell G.
Abstract: The ability to make controlled patterns of magnetic structures within a nonmagnetic background is essential for several types of existing and proposed technologies. Such patterns provide the foundation of magnetic memory and logic devices, allow the creation of artificial spin‐ice lattices, and enable the study of magnon propagation. Here, a novel approach for magnetic patterning that allows repeated creation and erasure of arbitrary shapes of thin‐film ferromagnetic structures is reported. This strategy is enabled by epitaxial Fe0.52 Rh0.48 thin films designed so that both ferromagnetic and antiferromagnetic phases are bistable at room temperature. Starting with the film in a uniform antiferromagnetic state, the ability to write arbitrary patterns of the ferromagnetic phase is demonstrated by local heating with a focused laser. If desired, the results can then be erased by cooling below room temperature and the material repeatedly re‐patterned. Abstract : By controlling the stoichiometry in epitaxial FeRh/MgO, the transition temperature from antiferromagnet to ferromagnet is tuned such that both phases are stable at room temperature. Focused pulsed laser heating is used to write and image arbitrarily shaped ferromagnetic patterns at ultrafast speeds, which can be erased by cooling the film below room temperature.